2018
DOI: 10.1038/s41598-018-21871-3
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-driven eco-friendly smart curtain based on infrared responsive graphene oxide-polymer photoactuators

Abstract: Photomechanical actuation is the conversion of light energy into mechanical energy through some smart materials. Infrared-responsive smart materials have become an emerging field of research due to easy availability and eco-friendly nature of their stimulus in the form of sunlight, which contains about 50% of near-infrared(nIR) making these materials useful at macro-scale photoactuator applications. Here, we demonstrate fabrication of highly versatile nIR triggered photoactuators based on graphene oxide/polyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…This is due to their huge potential as functional dyes towards a number of practical applications like organic photovoltaics, photomedicine, and molecular imaging . In the field of organic photovoltaics, dyes capable of absorbing NIR radiation are crucial for harvesting the energy of incident solar radiation, since nearly half of it falls in the visible to NIR range In photomedical applications like photodynamic therapy (PDT), the fluorescent organic dye has a dual role. It acts as a fluorescent probe for imaging of the tumor in vivo , followed by its photosensitizing action towards tumor destruction .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to their huge potential as functional dyes towards a number of practical applications like organic photovoltaics, photomedicine, and molecular imaging . In the field of organic photovoltaics, dyes capable of absorbing NIR radiation are crucial for harvesting the energy of incident solar radiation, since nearly half of it falls in the visible to NIR range In photomedical applications like photodynamic therapy (PDT), the fluorescent organic dye has a dual role. It acts as a fluorescent probe for imaging of the tumor in vivo , followed by its photosensitizing action towards tumor destruction .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Gr/PC composites have demonstrated their use for potential applications in smart materials. Leeladhar and Singh [114] prepared a GO/PC composite material with a double-layer structure that exhibited a smart response to infrared light. erefore, the composite material was able to act as a light actuator, 8 Advances in Materials Science and Engineering which could be used in applications such as sunlight-driven curtains, infrared light-driven curtains, and boxes that automatically fold upon exposure to light.…”
Section: Applications Of Graphene/polymer Composite Materialsmentioning
confidence: 99%
“…The first approach is where the carbon materials directly serve as photoelectronic actuators . Another approach is to incorporate carbon materials into other soft material matrixes to form a homogeneous composite through solution mixing/casting, in situ polymerization or wet spinning . The third approach is to use carbon materials as individual photothermal layers in bilayer structured photothermal actuators via vacuum filtration and high temperature curing …”
Section: Carbon‐based Soft Materials For Photoresponsive Actuator Designmentioning
confidence: 99%
“…In contrast, the vacuum filtration method is a simple and fast processing approach for layered‐structure fabrication. For instance, Leeladhar et al reported a bilayer structure integrating GO and PC membrane via vacuum filtration in which the PC membrane functioned as both substrate and filter . This bilayer structure showed deflection from the equilibrium state under both real sunlight and IR illumination (the maximum deflection was 12 mm in 3 s with a bending curvature of 0.33 cm −1 ) and demonstrated real‐world application of actuators driven by sunlight rather than an artificial light source.…”
Section: Carbon‐based Soft Materials For Photoresponsive Actuator Designmentioning
confidence: 99%